Literatura, vida pública e modernidade: um estudo sobre Othon Lobo da Gama d'Eça - Furtado, Tamires Quesada [UNIFESP] (2015)
This thesis aims to analyze the literature, the publications and the speeches of Othon Lobo Gama D' Eça's (1892-1965), a Santa Catarina writer. The period reflected in his work relates to an urban transformation process that occurred in the city of Florianópolis and in the state of Santa Catarina in the first half of the twentieth century. Leading figure in Santa Catarina's scenario, Othon D' Eça was a writer, a member of Santa Catarina's Academy of Letters, the secretary of State's Public Security, a law professor and a politician, having also been provincial head of Integralism. This work intends to propose some interpretations of the author's intellectual production, linking the historical context to Othon D'Eça's biography, publications, notes and speeches, showing some of the dilemmas of modernization in Florianópolis in the decades between 1920 and 1950.